The Preservations of Grief in Karen Jones’ The Anatomy of The Aftermath - Pasopati, Rommel Utungga; Aprilla, Evania Nur; Wijaya, Kusuma; Kartiningsih, Rindrah; Hariyono, Hariyono (SALIENCE: English Language, Literature, and Education Journal, 2024)
This paper is focusing on the representation of Grief in the short story of Anatomy of the Aftermath by Karen Jones. Grief is an emotional experience triggered by the loss of something or someone that a person loves, often involving the process of detachment. Then, grief also helps individuals feel closer to the object of love, honor their memories, or fill the void left behind. Karen Jones' flash fiction explores the story of a woman who feels sadness, regret, and longing for her husband's voice after his death. Through qualitative method, this article explores symbols and motifs of the woman's desire to hear her husband's voice and the love that still exists between them despite their separation. Through Kubler Ross’ theory of grief, this paper suggests that if a person can navigate the process well, they can experience normal and healthy grief. In conclusion, it is noted that grief could have two faces of being constructive and destructive. Both aspects are thickly indicated in Jones’ flash fiction.